2017
DOI: 10.1016/j.tafmec.2017.06.005
|View full text |Cite
|
Sign up to set email alerts
|

A fracture mechanics approach to characterising the environmental stress cracking behaviour of thermoplastics

Abstract: Environmental stress cracking (ESC) is known to affect certain thermoplastics and occurs under simultaneous exposure to both applied stress and a hostile environment. The combination of these can cause a crack to form from a flaw in the material; upon reaching a critical size, the crack may accelerate thus causing catastrophic failure in the component. Various tests have been utilised to measure the resistance of different polymers to ESC, but these are often material- and application-specific and overlook the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 11 publications
0
21
0
Order By: Relevance
“…Fracture mechanics has been successfully applied to the study of fracture in viscoelastic materials, as reported in several instances in the existing scientific literature [11][12][13][14]. Its use has been extended directly to study ESC of several systems [15,16], including: polystyrene in oil [17][18][19], polyethylene in various detergents [20][21][22] and polyethyleneterephtalate in sodium hydroxide [23].…”
Section: Introductionmentioning
confidence: 99%
“…Fracture mechanics has been successfully applied to the study of fracture in viscoelastic materials, as reported in several instances in the existing scientific literature [11][12][13][14]. Its use has been extended directly to study ESC of several systems [15,16], including: polystyrene in oil [17][18][19], polyethylene in various detergents [20][21][22] and polyethyleneterephtalate in sodium hydroxide [23].…”
Section: Introductionmentioning
confidence: 99%
“…From the intersection of the air and environment branches, critical interaction times * and critical crack growth rates ̇ * were evaluated. These parameters, previously observed in (Chang and Donovan, 1990;Ward et al, 1991;Ayyer, Hiltner and Baer, 2008;Andena et al, 2013;Kamaludin et al, 2017), reveal if a given environment will influence the fracture behaviour of a polymer. As a matter of fact, Environmental Stress Cracking will occur under conditions of or corresponding to fracture times that are longer than * and propagation rates lower than ̇ * .…”
Section: Resultsmentioning
confidence: 55%
“…This approximation, which constitutes the basis of the so-called pseudo-elastic approach, was found to be adequate to describe the behaviour of a variety of polymeric materials, among which were also some nonlinear viscoelastic materials. For instance, and were used for the analysis of the Slow Crack Growth (SCG) and Environmental Stress Cracking (ESC) of several polymers (Williams and Marshall, 1975;Frassine et al, 1996;Kamaludin et al, 2017), including: -toughened polymethyl methacrylate (Mariani et al, 1996;Pini et al, 2018) -high impact polystyrene (Andena et al, 2013(Andena et al, , 2016Kamaludin et al, 2016) -polybutene (Andena et al, 2009) -polyethylene (Chan and Williams, 1983;Brown, 1986, 1987;Chang and Donovan, 1989;Rink et al, 2003;Frank, Pinter and Lang, 2009;Contino et al, 2016Contino et al, , 2018Kamaludin et al, 2016) Assumptions on the validity of these two fracture parameters and of Equation (1) are supported by the accurate description of the fracture behaviour of the polymers considered in these works.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, we assumed that the hydrogen in the material acted as the external load or residual stress. An additional load was needed to form a stress concentration around the crack tip during the crack propagation [21]. In this experiment, the hydrogen charged into the sample had the effect of a load, promoting the crack propagation [22][23][24].…”
Section: Mn Simentioning
confidence: 99%
“…The decrease in K IC due to hydrogen atoms was verified by MD simulations, as shown in Figures 14 and 15. Moreover, the hydrogen atoms can be driven to the crack tip by stress [35], as indicated by Equation (21), as the location of the crack tip is the place with the highest stress value around the crack:…”
Section: Fracture Toughness With Hydrogenmentioning
confidence: 99%